1999
DOI: 10.1038/sj.bjc.6690810
|View full text |Cite
|
Sign up to set email alerts
|

Expression of MAGE-1 and -3 genes and gene products in human hepatocellular carcinoma

Abstract: MAGE gene family encodes peptides recognized by autologous cytotoxic T lymphocytes in a major histocompatibility complex (MHC) class-I restricted fashion. In the present study, we have performed reverse-transcription polymerase chain reaction (RT-PCR) for the genes, as well as immunohistochemical analysis and Western blotting of MAGE-1 and -3 proteins in 33 surgically resected hepatocellular carcinomas (HCCs). MAGE-1 and -3 mRNAs were constitutively expressed exclusively in 78 and 42% of HCCs respectively. On … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
1

Year Published

2000
2000
2005
2005

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 29 publications
1
26
1
Order By: Relevance
“…Despite improvement in sonographic examinations and therapy for HCC, the outcome generally remains unsatisfactory. Recently, the expression of CT antigen-encoding genes in HCC tissues has been reported by several laboratories (7)(8)(9)(10). Our own data have revealed that mRNA for at least 20 CT antigens can be detected in HCC tissues.…”
Section: Introductionmentioning
confidence: 66%
“…Despite improvement in sonographic examinations and therapy for HCC, the outcome generally remains unsatisfactory. Recently, the expression of CT antigen-encoding genes in HCC tissues has been reported by several laboratories (7)(8)(9)(10). Our own data have revealed that mRNA for at least 20 CT antigens can be detected in HCC tissues.…”
Section: Introductionmentioning
confidence: 66%
“…One male patient of 36 malignant melanoma patients with stage IV lung metastasis had antibody against TSGA10. CT antigens generally induce a low frequency of antibody responses in cancer patients irrespective of the high frequency of expression of some CT antigens such as MAGE-1 (80%) in HCC (13), SSX (75%) in synovial sarcoma (34) with the exception of NY-ESO-1 (31). Wang et al (40) isolated 55 different antigens by SEREX-screening 4 HCC cDNA libraries with autologous or allogeneic sera.…”
Section: Discussionmentioning
confidence: 99%
“…12,13 MAGE expression has been found in a wide array of neoplastic lesions and is most prevalent in malignant melanomas, several types of carcinomas, and certain sarcomas. [14][15][16][17][18][19][20] NY-ESO-1 21,22 has been isolated in esophageal carcinoma but has also been found in several other malignancies, such as melanoma; neuroblastoma; carcinoma of the ovary, breast, and lung; and in synovial sarcoma. [23][24][25][26][27][28][29] The CT7 antigen was identified by the SEREX approach using a melanoma cell line SK-MEL37 and allogeneic sera from a melanoma patient.…”
mentioning
confidence: 99%